Selectivity and sublethal effect of botanical extracts on adults of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Gladenucci, Joanina; Pernambuco Filho, José Carlos de Almeida; Bueno, Regiane Cristina de Oliveira Freitas; Bonfim, Filipe Pereira Giardini (EntomoBrasilis, 2020)
The objective was to assess the selectivity and sublethal effect of botanical extracts on adults of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). Plant species used: Rosmarinus officinalis L., Mikania glomerata Spreng., Varronia curassavica Jacq., Chenopodium ambrosioides L., Vermonia polyanthes Spreng., Plectranthus amboinicus Spreng., Tetradenia riparia Codd., Artemisia absinthium L., Cymbopogon citratus Stapf. Plant material were reared in laboratory and leaves collected during the morning were used to prepare the extracts as following: 100 g of leaves from each plant were macerated and immersed in 300 mL of triple-extracted methyl alcohol and evaporated on rotavapor. Then, 250 mg of crude extract was diluted in 1000 mL of water. The experimental design for selectivity was done in randomized blocks with five repetitions, following a standardized protocol of the International Organization for Biological Control (IOBC) and accordingly classified. In sublethal effect, the design was completely randomized with twenty repetitions, where the eggs exposed to parasitism were sprayed with the treatments. In both experiments the control was twofold (water and chlorpyrifos). Regarding selectivity, the botanical extracts of M. glomerata, C. ambrosioides, V. polyanthes, P. amboinicus, A. absinthium and C. citratus were classified as slightly harmful (class 2), chlorpyrifos as moderately harmful (class 3). In the evaluation of sublethal effects, the botanical extracts of C. ambrosioides and C. citratus initially presented reduced number of parasitized eggs, reduction in total parasitized eggs and female longevity. It can be concluded that C. citratus botanical extract has small selectivity and causes sublethal effects on T. pretiosum adults.